Spinal Cord Stimulation Improves Functional Outcomes in Children With Complex Regional Pain Syndrome: Case Presentation and Review of the Literature. Issue 6 (13th April 2020) - Bakr, Salma M.; Knight, James; Johnson, Sarah K.; Williams, Amy E.; Tolley, James A.; Raskin, Jeffrey S.
Abstract: Background: In the pediatric population, complex regional pain syndrome (CRPS) is a debilitating chronic pain syndrome that is classically treated with escalating polypharmacy and physical therapy. Failure of therapy is often encountered in both adult and pediatric patients with CRPS, after which invasive neuromodulatory therapy might be considered. Intrathecal drug delivery systems and spinal cord stimulation (SCS) have been reported in the literature as forms of neuromodulation effective in adult CRPS; however, SCS remains inadequately researched and underreported in the pediatric CRPS population. Owing to the differences in patient population characteristics and the specific vulnerability of adolescents to drugs that might be used to manage refractory cases, including but not limited to opioids, we believe that early effective pain management without the use of chronic pain medications is of paramount importance. Methods: Recent evidence suggests that neuromodulation can be useful toward improving function and managing pain, while also reducing medication use in chronic pain patients. A representative case a review of the literature is performed. Results: We report the effective treatment of CRPS in a pediatric patient following implantation of an SCS device typifying the improved pain scores, decreased medication use, and substantially improved functional abilities in pediatric patients following SCS. Conclusions: The manuscript objective is to stimulate a discussion for SCS use earlier in the therapeutic management of CRPS in children.